2019
DOI: 10.1177/1179548419835788
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator Genotype, Not Circulating Catecholamines, Influences Cardiovascular Function in Patients with Cystic Fibrosis

Abstract: Background: Cystic fibrosis (CF) is a genetic disease affecting multiple organ systems of the body and is characterized by mutation in the gene coding for the cystic fibrosis transmembrane conductance regulator (CFTR). Previous work has shown that a single dose of aβ-agonist increases cardiac output (Q) and stroke volume (SV) and decreases systemic vascular resistance (SVR) in healthy subjects. This effect is attenuated in patients with CF; however, the mechanism is unknown. Potential explanations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…1 B and 4 A) and a decreased aortic compliance ( Figs. 1 C and 4 A,c) are consistent with the findings from Bisch et al [4] and also with the results from previous in vitro studies by Robert et al that arteries from cftr −/ − mice became significantly more constricted than that from cftr + / + mice in response to vasoactive agents [ 3 , 19 ]. For our in vivo experiments we did not examine whether the endothelial function of aorta or mesenteric arteries from cftr −/ − mice remains normal or not since Robert et al reported that arteries with or without endothelium from cftr −/ − mice became significantly more constricted than that from cftr + / + mice in response to vasoactive agents and thus CFTR activation contributed to an endothelium-independent vasorelaxation [ 3 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…1 B and 4 A) and a decreased aortic compliance ( Figs. 1 C and 4 A,c) are consistent with the findings from Bisch et al [4] and also with the results from previous in vitro studies by Robert et al that arteries from cftr −/ − mice became significantly more constricted than that from cftr + / + mice in response to vasoactive agents [ 3 , 19 ]. For our in vivo experiments we did not examine whether the endothelial function of aorta or mesenteric arteries from cftr −/ − mice remains normal or not since Robert et al reported that arteries with or without endothelium from cftr −/ − mice became significantly more constricted than that from cftr + / + mice in response to vasoactive agents and thus CFTR activation contributed to an endothelium-independent vasorelaxation [ 3 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Disruption of CFTR not only affects the response of VSMCs to vasoactive agents but also prevents the cAMP-dependent vasorelaxasion [3] . Consistent with these in vitro findings, it has been recently reported that the most common mutation ( F508) of CFTR is associated with an increased systemic vascular resistance (SVR) at rest in CF patients when compared with healthy subjects [4] . In contrast to these findings, however, Peotta et al reported that in a mouse model of heterozygous CFTR F508 mutation the aortic contractility was decreased and the arterial pressures were significantly lower than the wild-type C57BL/6 controls, with the greatest effect seen at the time of dark-to-light cycle transition (mean difference of 10 mmHg) [7] .…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Whether these changes were clinically significant cannot be determined from the information available, but the single case of bradycardia reported was asymptomatic [ 45 ]. In one study, people with CF were found to have a higher baseline heart rate when compared to healthy controls [ 119 ]; therefore, correction of CFTR function may theoretically reduce heart rate. However, again, this heart rate-lowering effect is seemingly unique to LUM/IVA.…”
Section: Discussionmentioning
confidence: 99%